KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM MENYELESAIKAN SOAL NUMERASI DITINJAU DARI TIPE KEPRIBADIAN SENSING DAN INTUITIVE - Dewi, Sri Kusuma; Rahaju, Endah Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students’ critical thinking ability can be developed through solving numeracy literacy problems. Critical thinking ability can be influenced by personality factors, including sensing and intuitive types. This research used a qualitative descriptive approach that aimed to describe students’ critical thinking ability in solving numeracy problems in terms of sensing and intuitive personality types. The research subjects consisted of two female students from Class VIII-B at SMP Labschool UNESA 2 who had high and comparable mathematical abilities with one student having a sensing personality type and the other having an intuitive personality type. The data were collected using a personality questionnaire, a mathematics ability test, a critical thinking ability test, and an interview. The data were analyzed based on Perkins & Murphy’s critical thinking indicators, namely clarification, assessment, inference, and strategy. The research results showed that student with a sensing type met three indicators: assessment, inference, and strategy. In contrast, student with an intuitive type met one indicator: inference. (a) For the clarification indicator, both sensing and intuitive students were unable to identify what was known and what was asked in the questions completely. (b) for the assessment indicator, sensing student was able to identify and explain the reasons for choosing some information to solve the problem. In contrast, intuitive student was only able to identify the information used. (c) For the inference indicator, both students were able to show the relationships between the information, deduce the steps needed to solve the problem, and explain the final answer to the problem. (d) For the strategy indicator, sensing student was able to write down the formula accurately and completely, write down and explain the solution steps systematically, and evaluate the solution steps they had used. In contrast, intuitive student was only able to explain the solution steps.